U.S. Copyright Office's Questions about Generative AI. - Samuelson, Pamela (Communications of the ACM, 2024)
An opinion is presented in which the author discusses the U.S. Copyright Office's initiative, which invited written comments to questions concerning generative artificial intelligence (AI) and copyright issues published in a Notice of Inquiry (NOI) on August 30, 2023. It is noted that the Office received around 10,000 comments in response to its inquiry. Some of the comments which focus on topics including copyright infringement and training data as well as training data disclosure requirements are discussed